COVID-19 pandemic effects on health worker’s mental health: Systematic review and meta-analysis - Claudia Aymerich; Borja Pedruzo; Jose Luís Pérez; Maria Laborda; Jon Herrero; Jorge Blanco; Gonzalo Mancebo; Lucía Andrés; Olatz Estévez; Maitane Fernandez; Gonzalo Salazar de Pablo; Ana Catalan; et al. (European Psychiatry, 2022)
Abstract